2018
DOI: 10.20524/aog.2018.0284
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognized extratumoral features of colorectal cancer challenge the current tumor-node-metastasis staging system

Abstract: One of the most common malignant tumors in humans, colorectal cancer has been extensively studied during the past few decades. Staging colorectal cancer allows clinicians to obtain precise prognostic information and apply specific treatment procedures. Apart from remote metastases, the depth of tumor infiltration and lymph node involvement have traditionally been recognized as the most important factors predicting outcome. Variations in the molecular signature of colorectal cancer have also revealed difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…Specific guidelines regarding liver metastasis were revised in 2018 in order to improve the diagnosis and treatment strategy, including the overall clinical evaluation, personalized treatment goals, and comprehensive treatment protocol, in order to prevent the occurrence of liver metastases, and improve the resection rate of liver metastases and survival [57]. Although experts of different countries have investigated their treatment strategy for colorectal cancer thoroughly for many years, the TNM staging system is still commonly regarded as an essential tool to predict oncologic outcomes [58]. It has made an essential contribution to the clinical management of cancer patients over the past 50 years [59], but are we sure it delivers what is needed to provide adequate advice in the 21st century?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific guidelines regarding liver metastasis were revised in 2018 in order to improve the diagnosis and treatment strategy, including the overall clinical evaluation, personalized treatment goals, and comprehensive treatment protocol, in order to prevent the occurrence of liver metastases, and improve the resection rate of liver metastases and survival [57]. Although experts of different countries have investigated their treatment strategy for colorectal cancer thoroughly for many years, the TNM staging system is still commonly regarded as an essential tool to predict oncologic outcomes [58]. It has made an essential contribution to the clinical management of cancer patients over the past 50 years [59], but are we sure it delivers what is needed to provide adequate advice in the 21st century?…”
Section: Discussionmentioning
confidence: 99%
“…These previously unrecognized features were closely related to the way cancerous cells interact with the surrounding stroma and obtain their potential for invasiveness [70]. These characteristics included tumor budding, poorly differentiated clusters, extramural vascular (vein) invasion, perineural invasion, tumor deposits, and mucin pools [58]. This discrepancy in the molecular signature of colorectal cancer has also revealed differences in phenotypic aggressiveness and therapeutic response rates [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other novel histopathological parameters are also being explored as potential prognostic biomarkers for colorectal cancer, such as tumor budding (TB), poorly differentiated clusters (PDCs), extramural vascular (vein) invasion (EMVI), perineural invasion (PNI), tumor deposits (TDs), mucin pools (MPs), and extranodal extension of nodal metastasis (ENE), but some of these are yet to be fully investigated in larger phase trials for their association with prognosis of colorectal cancer. For example, ENE has been reported to be associated with a significantly increased risk of recurrence and mortality in a meta-analysis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confirmed this evidence in CRC. It has been suggested that TDs have negative prognostic value but are not sufficiently categorized in the current TNM staging and the number and/or presence of the TD should be added to the number of LNMs to define the final N stage creating a specific category for TDs with LNM, which could be called category N2c or N3[ 37 - 41 ].…”
Section: Lymphatic Drainage In Crcmentioning
confidence: 99%